2019
DOI: 10.3892/etm.2019.7848
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key gene modules and transcription factors for human osteoarthritis by weighted gene co‑expression network analysis

Abstract: Osteoarthritis (OA) is one of the most prevalent causes of joint disease. However, the pathological mechanisms of OA have remained to be completely elucidated, and further investigation into the underlying mechanisms of OA development and the identification of novel therapeutic targets are urgently required. In the present study, the dataset GSE114007 was downloaded from the Gene Expression Omnibus database. Based on weighted gene co-expression network analysis (WGCNA) and the identification of differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 74 publications
2
20
0
1
Order By: Relevance
“…Besides, KEGG pathways of the overlapping DEGs revealed that these hub genes were mainly enriched in pathways of PI3K-Akt, focal adhesion, and osteoclast differentiation. The results of the present study were reasonable and consistent with the results of previous studies, which have also suggested that PI3K-Akt signaling pathway [2729], focal adhesion [30], and osteoclast differentiation [31, 32] are involved in the pathogenesis of OA.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, KEGG pathways of the overlapping DEGs revealed that these hub genes were mainly enriched in pathways of PI3K-Akt, focal adhesion, and osteoclast differentiation. The results of the present study were reasonable and consistent with the results of previous studies, which have also suggested that PI3K-Akt signaling pathway [2729], focal adhesion [30], and osteoclast differentiation [31, 32] are involved in the pathogenesis of OA.…”
Section: Discussionsupporting
confidence: 93%
“…These 93 TFs included JUN, EGR1, JUND, FOSL2, MYC, KLF4, RelA, and FOS. Another study also identified JUN, JUND, MYC, and FOS as the four TFs that are central in regulating signaling pathways in OA knee cartilage [43].…”
Section: Transcription Factors In Oamentioning
confidence: 95%
“…In OA, multiples of these TFs are differently expressed. For example, expression of AP-1, which is a dimeric TF primarily composed of FOS and JUN proteins, has been shown to be increased in knee OA cartilage [42,43]. Inhibition of AP-1 activity in vitro by the use of the small molecule inhibitor T-5224 inhibited MMP3 and MMP13 production in SW1353 chondrocytes [67].…”
Section: Transcription Factors Related To Ecm Metabolismmentioning
confidence: 99%
“…Weighted gene co-expression network analysis (WGCNA) is a systematic biological method that delineates correlations between genes and clinical traits [16]. It identifies highly correlated genes to investigate potential biological functions [17,18].…”
Section: Introductionmentioning
confidence: 99%